Pathogen-Associated Molecular Patterns: The Synthesis of Heptose Phosphates and Derivatives - Williams, Dean; Jamshidi, Mohammad P.; Sauvageau, Janelle (Synthesis, 2021)
Lipopolysaccharide biosynthesis metabolites, such as d-glycero-β-d-manno-heptopyranosyl 1,7-diphosphate, d-glycero-β-d-manno-heptopyranosyl phosphate, and adenosine 5′-(l-glycero-β-d-manno-heptopyranosyl)diphosphate, have been found to activate NF-κB via alpha-kinase 1 and TRAF-interacting protein with forkhead associated domain. This axis has been determined as a novel pathway of innate immunity yet to be targeted for immunomodulatory treatment approaches. Key in understanding this new axis has been the ability to synthesize these metabolites. The design of synthetic analogues and probes have also been published not only to design new drugs, but also to gain insight into the mechanism of action for these compounds. The focus of the present review is the synthesis of heptose phosphate metabolites as well as synthetic analogues and probes.1 Introduction2 Synthesis of d-glycero-d-manno-Heptose2.1 Using d-Mannose as Starting Material2.2 Using d-Ribose as Starting Material2.3 Using 2,2-Dimethyl-1,3-dioxan-5-one as Starting Material3 Synthesis of l-glycero-d-manno-Heptose3.1 Using d-Mannose as Starting Material3.2 Using 2,2-Dimethyl-1,3-dioxan-5-one as Starting Material3.3 Using l-Lyxose as Starting Material4 Synthesis of Heptose Phosphates4.1 Synthesis of d-glycero-β-d-manno-Heptose 1,7-Diphosphate4.2 Synthesis of Heptose Phosphate Derivatives4.2.1 Development of Scaffolds for Conjugation4.2.2 Development of Heptose Phosphates Derivatives for Cell Intake and Metabolic Stability5 Conclusion and Outlook
Keywords: heptose diphosphate; heptose monophosphate; ADP-heptose; metabolites; pathogen associated molecular patterns